Der Abfall von der polnischen Nationalität und die strafrechtliche Verantwortlichkeit in Polen ab 1945. Die Problematik der sog. Deutschen Volksliste in den besetzten Gebieten 1939 bis 19451 (Kronika Bydgoska, 2021)
This article describes the topic of a mass naturalization of Polish citizens during the occupation of the Republic of Poland in 1939–1945. It also indicates legal bases used by the occupying forces in order to implement the so-called reGermanization of the Occupied Eastern Territories and the actual application of these laws. Finally, the author focuses his attention on the situation in Poland after 1945. During the postwar years, the Polish lawmakers used to treat the Germanized Poles as enemies of the people, as ethnic Germans. Only after implementation of the amnesty laws in the 1950s, they did not perceive these enemies of the people as offenders acting against the Polish nation.